Arterial hypertension treatment effectiveness in elderly patients - M. E. Statsenko; T. G. Shcherbakova; O. E. Sporova; S. V. Belenkova; Yu. V. Kalashnikova (Российский кардиологический журнал, 2008)
Six-month indapamide therapy was highly effective in 70 % of elderly patients with Stage I-II arterial hypertension (AH). In 30 %, a combination of indapamide with lisinopril was necessary for achieving target blood pressure (BP) levels. Indapamide therapy was associated with significant reduction in systolic and pulse BP, SBP variability, as well as with normalisation in circadian profile and morning dynamics of SBP and DBP. Twenty-four-week indapamide treatment resulted in significant reductions in left ventricular hypertrophy and aortal stiffness index, combined with nephroprotective effects. Indapamide did not affect carbohydrate, purine, and electrolyte metabolism. In elderly patients with AH, six-month indapamide therapy was linked to significant improvement in quality of life and cognitive and mnestic functioning